Do Parenting Style and Adolescents’ Self-esteem Contribute to Mental Health Problems among Young Adolescents in Malaysia? An Adolescents’ Perspective - Noordin, I.D.; Idris, I.B.; Hod, R.; Muhammad, N.A.; Mohd Yusoff, H.; Anuar, N.A.; Mohd Ghazali , Q. (IIUM Medical Journal Malaysia, 2020)
Introduction: Adolescence is a crucial phase in life, as this is the time when they are developing their identity, while at the same time forming relationships with others, including their family members. This study investigated adolescents’ mental health status in Malaysia and its associated factors including self -esteem and parenting style that are experienced by them. Materials and Methods: A cross-sectional study was conducted among 248 school-going adolescents aged 13 and 14 years in Selangor, Malaysia. The validated Malay version of the Strengths and Difficulties Questionnaire (SDQ) was utilized to assess adolescents’ mental health status. In addition, the adolescents’ self-esteem was also assessed using the Rosenberg Self-Esteem Scale Questionnaire while the Parental Bonding Instrument was used to assess their parent’s parenting style. Results: Almost 20% of the adolescents were found to have mental health problems such as emotional and conduct problems, hyperactivity disorder and peer problems. Using multivariate analysis, factors that were associated with mental health problems were family income (AOR=2.788, 95% CI=1.397, 5.563), adolescents’ self-esteem (AOR=0.799, 95% CI=0.668, 0.955) and their perception on parental control (AOR=1.175, 95% CI=1.020, 1.353). Conclusion: This study shows that one fifth of these adolescents had mental health problems. Low socio-economic factors, over controlling parents and poor self-esteem were associated with these problems. In conclusion, it is important to educate parents on effective parenting style, as improper parenting may cause psychological distress among adolescents. Improving families’ socioeconomic status and adolescents’ self-esteem can also enhance their mental health and well-being.